Pulse Response of an Ultracompact Grating-Based Monolithic Optical Compressor - C. Yang; E. Towe (IEEE Photonics Journal)
The pulse response of a novel monolithic optical compressor is computationally simulated using the finite-difference time-domain method of electromagnetism. This compact and robust compressor can be made from a solid block of fused silica with all necessary optical components integrated into it. A beam folding mechanism implemented through use of integral Bragg reflectors serves to further reduce the volume of the device. The monolithic compressor is shown to successfully compress dispersion precompensated 0.6-ps Gaussian input pulses to output pulses with a duration of 25 fs.